THE INFLUENCE OF TEACHER TEACHING STYLE, LEARNING ENVIRONMENT AND INTEREST IN LEARNING ON STUDENTS’ MOTIVATION AND LEARNING OUTCOMES - Soleh, Ardian; Gusnardi; Indrawati, Henny (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2025)
Learning outcomes are a crucial aspect of any learning process. Various factors, both internal and external, can affect student learning outcomes. This study aims to analyse the effect of teacher teaching style, learning environment, and interest in learning on motivation and learning outcomes of students in grades X, XI, and XII at SMA Negeri 1 Barumun and SMA Negeri 1 Sosa. The research was conducted from February to June 2023 with a descriptive quantitative approach. The data collection techniques used included questionnaires and documentation. A total of 90 students were selected as respondents through simple random sampling technique. Data analysis was conducted using variance-based Structural Equation Modeling (SEM) with the help of SmartPLS 3.0 software. The results showed that directly, the teacher's teaching style, learning environment, and learning interest affect learning outcomes through the mediating role of learning motivation. However, learning motivation does not have a direct effect on learning outcomes. Learning environment and learning interest were shown to influence learning outcomes through increasing learning motivation. This finding indicates that the right teacher teaching style that suits students' needs, a conducive learning environment, and high interest in learning can increase learning motivation, which in turn has a positive impact on student learning outcomes. The implications of this study emphasise the importance of improving the quality of teachers' teaching styles, creating a supportive learning environment, and developing students' interest in learning as strategies to encourage motivation and achieve optimal learning outcomes.